2010
DOI: 10.1007/s00170-010-2795-z
|View full text |Cite
|
Sign up to set email alerts
|

Tool edge radius effect on cutting temperature in micro-end-milling process

Abstract: The cutting temperature plays an important role in micro-scale cutting process due to the fact that the dimension of the micro-cutter is small and the value of micro-cutter wear is sensitive to temperature. In this paper, the temperature distribution of the micro-cutter in the micro-end-milling process has been investigated by numerical simulations and experimental approach. Micro-end-milling processes are modeled by the three-dimensional finite element method coupling thermal-mechanical effects. The microcutt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…In addition, the tribological behaviour of TiAlN coatings reported that it had a coefficient of friction μ = 0.7 [48]. Previous studies on modelling the machining process of Al2024-T alloy used coefficient of friction between 0.3 and 0.7 [30,[49][50][51]. Therefore, the coefficient of friction of 0.7 was selected after a vigorous mesh study where it was varied from 0.4 to 0.8 used in previous studies.…”
Section: Contact Loading and Boundary Conditionsmentioning
confidence: 99%
“…In addition, the tribological behaviour of TiAlN coatings reported that it had a coefficient of friction μ = 0.7 [48]. Previous studies on modelling the machining process of Al2024-T alloy used coefficient of friction between 0.3 and 0.7 [30,[49][50][51]. Therefore, the coefficient of friction of 0.7 was selected after a vigorous mesh study where it was varied from 0.4 to 0.8 used in previous studies.…”
Section: Contact Loading and Boundary Conditionsmentioning
confidence: 99%
“…In precision and ultraprecision machining, the feed rate is often in the same magnitude as the tool edge radius. The effect of the tool edge radius cannot be neglected because extensive experimental evidence has suggested that the tool edge radius significantly affects chip formation, 1-3 cutting forces, [4][5][6] cutting temperatures, 7 tool wear, 8 and surface integrity. 9 For example, Arif, Rahman, and San 5 found that tool edge radius affects crack propagation in the cutting zone in the ductile-mode machining of brittle materials, such as tungsten carbides.…”
Section: The Important Effect Of Tool Edge Radius In Machiningmentioning
confidence: 99%
“…In addition to 2D analysis, the 3D FEM method provides additional analysis material to explore the effect of the cutting tool on chip flow and burr formation [13]. A 3D FEM in dry micro milling process studied chip formation such as plastic chip flow, plastic strain, principle stresses, and temperatures of titanium alloy Ti-6Al-4V [14].…”
Section: Introductionmentioning
confidence: 99%
“…A 3D FEM in dry micro milling process studied chip formation such as plastic chip flow, plastic strain, principle stresses, and temperatures of titanium alloy Ti-6Al-4V [14]. Another study [13] with 3D FEM investigated the effect of the cutting edge radius on temperature distribution, effective stress and simulated cutting forces in Al2024-T6 micro milling. Abouridouane et al [15] studied microstructure-based multiphase FEM of micro drilling ferritic-pearlitic carbon steels.…”
Section: Introductionmentioning
confidence: 99%